Regeneration of oreomunnea mexicana (Juglandaceae), a threatened relict species of the sierra juarez cloud forest, oaxaca, Mexico (2019)
Oreomunnea mexicana (Stand.) J.F. Leroy is a relict species, threatened and a key species for cloud ecosystem functionof the Sierra Juárez, Oaxaca, the most extensive and best conserved in Mexico. This study includes a diagnostic on two critical stages of the process of population regeneration of O. mexicana. To this end, it analyzed the: 1) production, dispersion, viability and germination of seeds, 2) effect of predation on the growth and survival of the seedlings, and 3) effect of environmental variables (soil, canopy structure and solar radiation) on the regeneration of the species. The study was made from 2014 to 2015 in the cloud forest of Santiago Comaltepec, Oaxaca, Mexico, in two locations (San Bernardo and El Orquidiario). Differences in seed production were found between years and between locations, as well as low seed viability and a high percentage of seed parasitism. The establishment and growth of the seedlings are subject to find suitable microhabitats, since seedlings have specific illumination and soil requirements. The high edaphic specificity faced by the species could be a key factor for its fragmented and discontinuous distribution in Sierra Juárez. Further population regeneration studies are recommended to increase knowledge of the species and thereby achieve its conservation. © 2019, Instituto de Ecologia, A.C. All rights reserved.